Physics / For First Examinations - Davies David; Mccullough David (Holmes Mcdougall Ltd, 1981)
Preface, Units, Astronomy, Light, Using Light, Waves, What is Matter?, Heat, Using Heat, Pushing and Pulling, Movement, Liquids and Gases, Magnetism, Electricity, Supply and Control of Electricity, Energy of the Atom, Index.